Stereotactic Body Radiotherapy for Oligometastatic Prostate Cancer Recurrence: A Meta-analysis - Viani, Gustavo A.; Arruda, Caio V. [UNESP]; Hamamura, Ana C.; Faustino, Alexandre C.; Freitas Bendo Danelichen, Anielle; Guimarães, Flavio S. (Wolters Kluwer, 2020)
Purpose:The purpose of this study was to evaluate the treatment efficacy of stereotactic body radiotherapy (SBRT) in oligometastatic prostate cancer recurrence and to assess whether there is any relationship between biologically effective dose (BED) and local control (LC).Materials and Methods:Eligible studies were identified on Medline, Embase, and the Cochrane Library, and the proceedings of annual meetings through May 2019 were also identified. A meta-regression analysis was performed to assess whether there is a relationship between BED and LC. In the univariate analysis, studies were separated by the study design, the number of metastatic sites, the site of metastases, radiotherapy machine, and prostate-specific antigen level at the time of SBRT. A P-value <0.05 was considered significant.Results:Twenty-three observational studies with a total of 1441 lesions treated were included in the meta-analysis. The proportional rate of LC, progression-free survival, and androgen deprivation-free survival was 0.976 (95% confidence interval [CI]: 0.96-0.98), 0.413 (95% CI: 0.378-0.477), and 20.1 months (95% CI: 14.5-25.6), respectively. In the meta-regression, a linear relationship between BED and LC was detected (P=0.017). Stratifying the BED into 3 levels (BED<100 Gy3, BED 100 to 130 Gy3, and BED>130 Gy3), a significant difference was observed between BED<100 Gy3 (LC=88%) versus BED>100 Gy3 (LC=96%). The rate of any acute and late grade ≥2 toxicity was 1.3% and 1.2%, respectively.Conclusions:The LC rate with SBRT was excellent with minimal severe acute/late toxicity. Our data suggest a dose relationship between BED and LC, with BED >100 Gy3 resulting in better rates of LC.
Keywords: oligometastases; prostate cancer; recurrence; stereotactic body radiotherapy